Structural interpretations of a flexible cold-active AMS8 lipase by combining small-angle X-ray scattering and molecular dynamics simulation (SAXS-MD) - Yaacob, Norhayati; Kamonsutthipaijit, Nuntaporn; Soontaranon, Siriwat; Thean, Adam Chor Leow; Raja Abd Rahman, Raja Noor Zaliha; Mohamad Ali, Mohd Shukuri (Elsevier, 2022)
Determining structure of highly flexible protein with multiple conformations can be challenging. This paper aims to combine molecular dynamics (MD) and small angle X-ray diffraction (SAX) techniques as a solution to overcome issues related to protein conformation in hardly crystallized protein. Based on prior studies, a cold-active lipase AMS8 was simulated in solvents showing stability in its N-terminal and high flexibility in its C-terminal. However, MD in its own algorithm could not explain the basis of macromolecule conformational transitions or changes related to protein through folding. Hence, by combining SAXS with MD, it is possible to understand the structure of flexible AMS8 lipase in natural space. Based on the findings, SAXS ab-initio model of AMS8 lipase was identified as a monomeric protein in which the optimized model of cold-active lipase AMS8 derived from SAXS data was found to be aligned with AMS8 homology model under series of MD timeframe.